Molecular characterisation of isolates of Metarhizium from locusts and grasshopers - Bridge, P.D.; Prior, C.; Sagbohan, J.; Lomer, C.J.; Carey, M.; Buddie, A. (Springer, 1997)
The relationships between 30 strains of Metarhizium were investigated by isoenzyme analysis, PCRRAPDs, and protease production. The strains included representatives of M. anisopliae, M. Flavoviride var. ¯avoviride and M. Flavoviride var. minus. Thirteen isolates conforming to M. Flavoviride from acridoid hosts and pathogenic to locusts and grasshoppers were shown to be a single, distinctive genotype with a pan-tropical distribution. In addition, the separation of M. Flavoviride var. minus as a host specific taxon distinct from European isolates of M. Flavoviride was also supported. The possibility of coevolution within some insect pathogenic populations is discussed.